(untitled) (Jurnal iSpectrum, 2025)
With the advancement of technology, Artificial Intelligence (AI) has rapidly evolved and expanded into various fields, including interior design. AI offers practical benefits such as efficiency in the design process, optimization of final renderings of buildings and spaces, as well as modelling materials and objects in 3D. With its ability to generate designs within seconds, AI is increasingly favoured by designers and industry professionals. From a policy perspective in design, management, business, and information technology systems, this study examines regulations and ethical considerations in the use of AI in the interior design industry. In the realm of design, policies related to copyright and intellectual property rights over AI-generated designs remain a subject of debate. In terms of management and business, the adoption of AI in interior design presents new challenges in standardizing designer competencies, shifting business models in design services, and its impact on traditional workforce roles. Information technology policies also play a role in regulating user data usage in AI, ensuring privacy, security, and algorithmic transparency in the design process. This study focuses on legal frameworks relevant to Indonesia, particularly regulations such as Law No. 28 of 2014 on Copyright, which does not fully recognize AI-generated works as individual property since AI is not considered a legal subject. Additionally, labour regulations, including Law No. 13 of 2003 on Manpower and the Omnibus Law No. 11 of 2020 on Job Creation, are relevant in analysing how AI may replace or alter the role of interior designers in the industry and how policies can protect workers from technological disruption. The aim of this study is to examine how Artificial Intelligence (AI) is utilized in the design process within the interior design field. Furthermore, this research analyses the advantages and disadvantages of AI implementation in design, focusing on aspects of efficiency, creativity, and the evolving role of interior designers in an increasingly digitalized industry. This study employs a literature review method by analysing various references from articles, scientific journals, and reputable sources on the application of AI in interior design. Additionally, it evaluates multiple AI applications used in interior design to gain a deeper understanding of how this technology contributes to the design process and assesses its strengths and weaknesses.